Morphological predictors of swimming speed performance in river and reservoir populations of Australian smelt Retropinna semoni. Issue 6 (12th October 2020) - Svozil, Daniel Phillip; Baumgartner, Lee J.; Fulton, Christopher J.; Kopf, Richard Keller; Watts, Robyn J.
Abstract: Dam construction is a major driver of ecological change in freshwater ecosystems. Fish populations have been shown to diverge in response to different flow velocity habitats, yet adaptations of fish populations to river and reservoir habitats created by dams remains poorly understood. We aimed to evaluate divergence of morphological traits and prolonged swimming speed performance between lotic and lentic populations of Australian smelt Retropinna semoni and quantify the relationship between prolonged swimming speed performance and morphology. Prolonged swimming speed performance was assessed for 15 individuals from each of three river and two reservoir populations of R. semoni using the critical swimming speed test (Ucrit ). Body shape was characterized using geometric morphometrics, which was combined with fin aspect ratios and standard length to assess morphological divergence among the five populations. Best subsets model‐selection was used to identify the morphological traits that best explain Ucrit variation among individuals. Our results indicate R. semoni from river populations had significantly higher prolonged swimming speed performance (Ucrit = 46.61 ± 0.98 cm s −1 ) than reservoir conspecifics (Ucrit = 35.57 ± 0.83 cm s −1 ; F1, 74 = 58.624, Z = 35.938, P  < 0.001). Similarly, R. semoni sampled from river populations had significantly higher fin aspect ratios (ARcaudal = 1.71 ± 0.04 and 1.29 ± 0.02 respectively; F(1, 74) = 56.247, Z = 40.107, P < 0.001; ARpectoral = 1.85 ± 0.03 and 1.33 ± 0.02 respectively; F(1, 74) = 7.156, Z = 4.055, P < 0.01). Best‐subset analyses revealed Ucrit was most strongly correlated with pectoral and caudal fin aspect ratios (R 2 adj = 0.973, AICc = 41.54). Body shape, however, was subject to a three‐way interaction among population, habitat and sex effects (F3, 74 = 1.038. Z = 1.982; P  < 0.05). Thus sexual dimorphism formed a significant component of unique and complex variation in body shape among populations from different habitat types. This study revealed profound effects of human‐altered flow environments on locomotor morphology and its functional link to changes in swimming performance of a common freshwater fish. While past studies have indicated body shape may be an important axis for divergence between lotic and lentic populations of several freshwater fishes, fin aspect ratios were the most important predictor of swimming speed in our study. Differences in body morphology here were inconsistent between river and reservoir populations, suggesting this aspect of phenotype may be more strongly influenced by other factors such as predation and sexual dimorphism.